Detection of Impaired Sympathetic Cerebrovascular Control Using Functional Biomarkers Based on Principal Dynamic Mode Analysis - Saleem, Saqib; Tzeng, Yu-Chieh; Kleijn, W. Bastiaan; Teal, Paul D. (Frontiers in Physiology, 2017)
This study sought to determine whether models of cerebrovascular function based on Laguerre- Volterra kernels that account for nonlinear cerebral blood flow (CBF) dynamics can detect the effects of functional cerebral sympathetic blockade. We retrospectively analysed continuous beat-to-beat blood pressure, middle cerebral blood velocity, and partial-pressure of end-tidal CO2 (PETCO2) recordings from eighteen healthy individuals who were treated with either an oral dose of the alpha1-adrenergic receptor blocker Prazosin or a placebo treatment. The global principal dynamic modes (PDMs) were analysed using Laguerre-Volterra kernels to examine the nonlinear system dynamics. Our principal findings were: 1) very low frequency (<0.03 Hz) linear components of first-order kernels for BP and PETCO2 are mutually coupled to CBF dynamics with the ability to separate individuals between control and blockade conditions, and 2) the gains of the nonlinear functions associated with low-pass and 0.03 Hz global PDMs for the BP are sensitive to sympathetic blockade. Collectively these results suggest that very low frequency global PDMs for BP may have potential utility as functional biomarkers of sympathetic neurovascular dysfunction which can occur in conditions like autonomic failure, stroke and traumatic brain injury.